A range‐wide monitoring programme for a critically endangered nomadic bird. (26th August 2021) - Stojanovic, Dejan; Rayner, Laura; Tulloch, Ayesha; Crates, Ross; Webb, Matthew; Ingwersen, Dean; Runge, Claire; Heinsohn, Robert
Abstract: Nomads challenge the prevailing approach to species conservation because their unpredictable resource‐driven movements hamper data collection. We developed a monitoring approach to address the conservation needs of critically endangered, nomadic regent honeyeaters Anthochaera phrygia, whose unpredictable movements occur at a continental scale. We used species distribution models that incorporated lagged effects of environmental variation on habitat suitability to refine and prioritise monitoring. By incorporating lagged effects of weather on occurrence, we identified a priority area within which we selected sites to survey. We undertook 1695 surveys in 2016 at 777 priority sites, and in 2017, we conducted a further 1434 surveys at 859 sites. We discovered nesting regent honeyeaters at new locations, locating 218 regent honeyeaters over two years. We validated performance of our priority mapping with the 2016–2017 survey results and the results of Crates et al. ( J. Wildl. Manage . 2017, 81, 669). Predictive performance of the priority monitoring range map was best at estimated model values of approximately 0.7 and declined at both higher and lower values. Water availability was an important predictor, but poor resolution of the underlying data used in SDMs (e.g. temporary water sources) may explain our model performance. By accounting for spatiotemporal weather variation, we show that regional habitat suitability within the range of regent honeyeaters varied dramatically among years. Incorporating dynamic weather conditions is a useful approach to designing monitoring programmes for nomads. Our approach shows how to compromise between the need to account for the dynamic environmental conditions that drive site occupancy of nomads and the practical logistic constraints of implementing monitoring with scarce resources. Abstract : Nomads challenge the prevailing approach to species conservation because their unpredictable resource‐driven movements hamper data collection. We developed a monitoring approach to address conservation needs of critically endangered, nomadic regent honeyeaters Anthochaera phrygia . Our approach shows how to compromise between the need to account for the dynamic environmental conditions that drive site occupancy of nomads and the practical logistic constraints of implementing monitoring with scarce resources.